Pengaruh Persepsi Guru Tentang Kepemimpinan Kepala Sekolah, Komunikasi, Motivasi Terhadap Kinerja Guru - Fery Desrian Octama; Nurdin Nurdin; Rahmah Dianti Putri (FKIP Unila, 2018)
The purpose of this study is to determine whether there is influence of principal leadership, communication and motivation on teacher performance in SMP Negeri 1 Batu Brak. The population of this study which amounted to 43. retrieval techniques This research using saturated sampling technique, where all respondents will be examined.,